1996
DOI: 10.1346/ccmn.1996.0440504
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Arsenate Competitive Adsorption on Kaolinite, Montmorillonite and Illite

Abstract: Abstract--The adsorption of arsenate (As(V)) on kaolinite, montmorillonite and illite was investigated at varying pH and competing anion concentration while holding As(V) concentration (6.7 x 10 7 M), clay suspension density (2.5 g L 1) and ionic strength (0.1 M NaC1) constant. The effects of 2 concentrations of phosphate (P) or molybdate (Mo) (6.7 X 10 -7 and 6.7 x 10 6 M) on As(V) adsorption envelopes (adsorption vs. pH) gave evidence for direct competitive adsorption (in the case of As(V) + P) and possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
130
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(145 citation statements)
references
References 40 publications
15
130
0
Order By: Relevance
“…Indeed, higher kaolinite content than for the other two soil clay fractions (Table 1) was found in this soil. The contribution of the typically lower SSA of kaolinite than montmorillonite and illite (Manning and Goldberg, 1996) was also detected in the lowest SSA of the Rollesbroich WDC sample compared with the other soil samples (Table 6). In the Rollesbroich WDC sample, the introduction of the kaolinite particle structure of lower aspect ratios (Wilkinson and Lead, 2007) possibly creates large pores in the compact arrangement of dominant illite thin platelets of higher aspect ratios (ratio of platelet diameter to thickness) in the WDC microstructure.…”
Section: Contribution Of Metal Oxide Nanoparticles To the Colloidal Pmentioning
confidence: 90%
“…Indeed, higher kaolinite content than for the other two soil clay fractions (Table 1) was found in this soil. The contribution of the typically lower SSA of kaolinite than montmorillonite and illite (Manning and Goldberg, 1996) was also detected in the lowest SSA of the Rollesbroich WDC sample compared with the other soil samples (Table 6). In the Rollesbroich WDC sample, the introduction of the kaolinite particle structure of lower aspect ratios (Wilkinson and Lead, 2007) possibly creates large pores in the compact arrangement of dominant illite thin platelets of higher aspect ratios (ratio of platelet diameter to thickness) in the WDC microstructure.…”
Section: Contribution Of Metal Oxide Nanoparticles To the Colloidal Pmentioning
confidence: 90%
“…3), favouring desorption from mineral surfaces including illite, which comprised 30 % of the crystalline mineralogical fraction (Fig. 2c) (Manning, 1996).…”
Section: Sequential Chemical Extractions and Solid-phase P Partitioningmentioning
confidence: 99%
“…By contrast, Devau et al (2011) hypothesized that the "negative" pH dependence at low pH was due to the intrinsic PO 4 -P sorption properties of the illite edge sites they believed were important for PO 4 -P sorption in these soils. Earlier work by Edzwald et al (1976) and Manning and Goldberg (1996) showed that illite displays a marked P sorption maximum at around pH 6. Weng et al (2011) attributed their results to synergistic effects of Ca 2+ adsorption to oxides and showed that a surface complexation model would predict a minimum in P solubility near pH 7 under the conditions of their study (these authors used 0.01 M CaCl 2 background electrolyte, which might have affected the results and interpretations).…”
mentioning
confidence: 96%